The Quantum Optics of Asymmetric Mirrors With Coherent Light Absorption - Dawson, Benjamin; Furtak-Wells, Nicholas; Mann, Thomas; Jose, Gin; Beige, Almut (Frontiers in Photonics, 2021)
The local observables of the quantised electromagnetic field near a mirror-coated interface depend strongly on the properties of the media on {\em both} sides. In macroscopic quantum electrodynamics, this fact is taken into account with the help of optical Green's functions which correlate the position of an observer with all other spatial positions and photon frequencies. Here we present an alternative, more intuitive approach and obtain the local field observables with the help of a quantum mirror image detector method [Furtak-Wells et al., Phys. Rev. A 97, 043827 (2018)]. In order to correctly normalise electric field operators, we demand that spontaneous atomic decay rates simplify to their respective free space values far away from the reflecting surface. Our approach is interesting, since mirror-coated interfaces constitute a basic building block for novel quantum photonic devices.